2008
DOI: 10.1542/peds.2007-1511
|View full text |Cite
|
Sign up to set email alerts
|

Improved Cognitive Development Among Preterm Infants Attributable to Early Supplementation of Human Milk With Docosahexaenoic Acid and Arachidonic Acid

Abstract: Supplementation with docosahexaenoic acid and arachidonic acid for very preterm infants fed human milk in the early neonatal period was associated with better recognition memory and higher problem-solving scores at 6 months.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
174
0
3

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 218 publications
(184 citation statements)
references
References 27 publications
7
174
0
3
Order By: Relevance
“…Eighteen of these studies were RCTs. [11][12][13][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29] Among nonrandomized studies, 4 were interventional studies with a control group [30][31][32][33] and the remaining 2 studies 8,34 did not test an intervention because they examined the association of BPD with LCPUFA concentrations in blood or in tracheal aspirates. Fifteen RCTs presented dichotomous outcomes.…”
Section: Overview Of Included Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Eighteen of these studies were RCTs. [11][12][13][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29] Among nonrandomized studies, 4 were interventional studies with a control group [30][31][32][33] and the remaining 2 studies 8,34 did not test an intervention because they examined the association of BPD with LCPUFA concentrations in blood or in tracheal aspirates. Fifteen RCTs presented dichotomous outcomes.…”
Section: Overview Of Included Studiesmentioning
confidence: 99%
“…Several studies examined .1 neonatal outcome at a time (Table 1). Only a few studies reported other relevant neonatal outcomes, such as number of days of ventilation, or the use or duration of supplementation oxygen, 13,20,22,27,28 patent ductus arteriosus, 12,20,23,[30][31][32] cholestasis, 31,32 or number of days of hospital admission. 8,11,13,18,31,32 Effect Estimates for Dichotomous Neonatal Outcomes…”
Section: Characteristics Of Exposure and Outcomesmentioning
confidence: 99%
See 1 more Smart Citation
“…Supplementation of DHA/AA to premature infants has been associated with positive effects on cognition in several studies. 20,[27][28][29][30][31] Conversely, 2 systematic reviews of supplementation with low-dose long chain polyunsaturated fatty acids (LCPUFAs) revealed no significant effects on cognition. 32,33 Recent systematic reviews request further randomized controlled trials (RCTs) with LCPUFAs and cognitive development in premature infants.…”
Section: What This Study Addsmentioning
confidence: 99%
“…Анализ результатов этих работ демонстрирует противоречивые результаты. В ряде работ ставится под сомнение необходимость обогащения ДЦПНЖК специализированных смесей для недоношен-ных детей [58,59]. Подчеркивается, что дизайн данных исследований был разноплановым, при этом выборка детей была недостаточна для получения достоверных данных, а состав и дозы добавляемых жирных кислот значительно отличались.…”
Section: обзор литературыunclassified